Synthesis of five-membered styryllactone derivatives and their cytotoxicity against jurkat-t leukemia cell line / Suraya Zulkepli - Zulkepli, Suraya (2013)
Fourteen five-membered styryllactone derivatives were conveniently synthesized in two steps via Swem oxidation and Wittig olefination, as the key reactions.Microwave-assisted synthesis of several phosphonium salts was achieved in good to excellent yields. Five-membered lactone aldehydes were synthesized through Swem oxidation. These syntheses were accomplished by treatment of unstable aldehydes with various substituted phosphonium ylides through Wittig reaction and led to (E)- and (Z)-five-membered styryllactone derivatives in moderate yield. These new styryllactones exhibited moderate cytotoxicity against Jurkat-T leukemia cell lines.Compounds (Z)- 183a, (Zi)-183b and (Z)-183g (IC50 = 60 |j.M) were found to be the most active. A structure-activity relationship study (SAR) indicates that steric effectsof some substituents on the aromatic ring lead to reduce the cytotoxicity of styryllactone derivatives/analogues.